2014
DOI: 10.1177/1078155214522143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of generic imatinib

Abstract: Overall, anecdotal concerns appear to be unfounded for generic imatinib approved in Canada and the EU. There is no evidence that these generic imatinib products are less effective than brand name imatinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Studies have shown no difference in water solubility, and absorption between generic and branded imatinib. 17 Three forms of imatinib are identified (α-, β-and γ-crystalline forms), of which the β polymorph is more thermodynamically stable. 18 The branded imatinib is in the β-crystal form, while the majority of generics have the α-form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown no difference in water solubility, and absorption between generic and branded imatinib. 17 Three forms of imatinib are identified (α-, β-and γ-crystalline forms), of which the β polymorph is more thermodynamically stable. 18 The branded imatinib is in the β-crystal form, while the majority of generics have the α-form.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports/series [2][3][4][5][6] raised concerns about its efficacy but refer to generics with questionable bioequivalence. 7 To date, there is no evidence that imatinib generics approved in North America and the European Union (EU) lack efficacy compared to the branded drug, even when comparing different imatinib crystal forms. 7 Several studies correlated imatinib plasma concentrations (IPC) with adequate treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…7 To date, there is no evidence that imatinib generics approved in North America and the European Union (EU) lack efficacy compared to the branded drug, even when comparing different imatinib crystal forms. 7 Several studies correlated imatinib plasma concentrations (IPC) with adequate treatment response. [8][9][10] Recommended therapeutic imatinib plasma concentration (IPC) is between 1000 µmol/L and 3000 µmol/L.…”
Section: Introductionmentioning
confidence: 99%
“…For example in Canada and Europe generic IM has been approved for CML recently. 2 However in Turkey, generic IM preparations are currently present. In Turkey, between original and generic molecules of TKI's there is a price difference because of the reimbursement policy.…”
Section: Introductionmentioning
confidence: 99%
“…The major concern for generic IM is its efficacy over the original drug, Glivec or Gleevec, although actually generics were shown to be bioequivalent in many basic studies. 2 Elucidation of the non-inferiority of generic imatinib over the original molecule is important for effective clinical decision making in CML. 3 The aim of this multi-center study is to assess the efficacy of generic IM over Glivec in terms of hematological, cytogenetic, and molecular responses in CML.…”
Section: Introductionmentioning
confidence: 99%